An Examination of African American NCAA DI-FBS Football Coaches: A Five-Year Update - Bopp, Trevor; Sagas, Michael (Journal of Intercollegiate Sport, 2012)
Past studies have concluded that institutional and access discrimination remain potential deterrents in achieving a more diverse and equal representation of racial minority head coaches in college football. This study sought to examine and compare the career paths of all DI-FBS coaches to determine the potential continued existence of discrimination and its impact. Findings revealed an overall positive shift in the representation of African American coaches, particularly at the assistant coach level. Thus, the coaching career paths of current head coaches and coordinators appear to be paving a more equitable path for assistant and future coaches. However, the data also portray the existence of both institutional and access discrimination. Such biases facilitate and maintain an underrepresentation of African American coaches; and while the increased acceptance of upper-level coaches with diverse racial, playing, and coaching backgrounds suggests a positive shift toward racial equality among coaches, the movement for a balanced representation perseveres.